Enhanced charge transport in Al-doped ZnO nanotubes designed via simultaneous etching and Al doping of H2O-oxidized ZnO nanorods for solar cell applications. Issue 16 (8th March 2019) - Pelicano, Christian Mark; Yanagi, Hisao
Abstract : Innovative design of Al-doped ZnO nanotubes with superior charge-transport properties via simultaneous etching and Al doping of H2 O-oxidized ZnO nanorods. Abstract : Herein, the simultaneous etching and Al doping of H2 O-oxidized ZnO nanorods (NRs) to generate Al-doped ZnO nanotubes (AZO NTs) is demonstrated. The innovative approach involves a facile one-step spin-coating of AlCl3 solution on top of the NRs. The polar (001) planes of ZnO were selectively etched due to the acidic nature of the AlCl3 solution, resulting in the transformation of NRs to NTs. At the same time, effective Al doping into the NTs was accomplished. Surface morphological analysis revealed gradual formation of NTs through additional AlCl3 coatings. Evidence of Al dopant inclusion and uniform distribution within NTs was established from XPS, XRD, Raman and EELS elemental mapping analyses. The HRTEM image and SAED pattern showed that the AZO NTs have a high-quality crystalline structure. Higher transmittance and a blue shift in absorption edge can also be observed in doped films indicating band gap broadening. A new green emission in the PL spectra of AZO NTs emerged due to the formation of oxygen vacancies. Most importantly, the AZO NTs showed higher electrical conductivity and electron mobility values compared with undoped ZnO NRs. Steady-state PL spectra of perovskite films on top of AZO films were quenched stronger than those of ZnO NRs, indicating faster electron transfer in the perovskite/AZO NTs interface. These results highlight the potential of AZO NTs as an electrode for solar cells and other optoelectronic devices. Ultimately, our approach offers an attractive strategy to enhance the charge-transport properties of nanostructured materials.